Physician practices in Accountable Care Organizations are more likely to collect and use physician performance information, yet base only a small proportion of compensation on performance data. (19th November 2019) - Rosenthal, Meredith; Shortell, Stephen; Shah, Nilay D.; Peiris, David; Lewis, Valerie A.; Barrera, Jacob A.; Usadi, Benjamin; Colla, Carrie H.
Abstract: Importance: It is critical to develop a better understanding of the strategies provider organizations use to improve the performance of frontline clinicians and whether ACO participation is associated with differential adoption of these tools. Objectives: Characterize the strategies that physician practices use to improve clinician performance and determine their association with ACOs and other payment reforms. Data Sources: The National Survey of Healthcare Organizations and the National Survey of ACOs fielded 2017‐2018 (response rates = 47 percent and 48 percent). Study Design: Descriptive analysis for practices participating and not participating in ACOs among 2190 physician practice respondents. Linear regressions to examine characteristics associated with counts of performance domains for which a practice used data for feedback, quality improvement, or physician compensation as dependent variables. Logistic and fractional regression to examine characteristics associated with use of peer comparison and shares of primary care and specialist compensation accounted for by performance bonuses, respectively. Principal Findings: ACO‐affiliated practices feed back clinician‐level information and use it for quality improvement and compensation on more performance domains than non‐ACO‐affiliated practices. Performance measures contribute little to physician compensation irrespective of ACO participation. Conclusion: ACO‐affiliated practices are using more performance improvement strategies than other practices, but base only a small fraction of compensation on quality or cost.